Nonlinear pricing strategies and competitive conditions in the airline industry - Hernandez, Manuel A.; Wiggins, Steven N. (Wiley, 2014)
This paper empirically examines the effect of competitive conditions on nonlinear pricing strategies in the airline industry. We use a unique data set to analyze the impact of concentration and the competitive pressures generated by Southwest and other low cost carriers on the relative prices within a menu of fares. The menu orders tickets by quality based upon cabin and ticket restrictions. We analyze the ratio of fares charged for various qualities within the menu to the fares charged for the lowest quality nonrefundable, restricted tickets. We observe a fare compression for only the highest fares on only the most concentrated (i.e., monopoly) routes. This result is something of a puzzle given a monopolist's market power. We find, however, that actual and potential competition from Southwest reduces low end fares and generally leads to substantial fare compression throughout the fare menu. (JEL L11, L93)